Effect of injection pressure and fuel mass on wall-impinging ignition and combustion characteristics of heavy-duty diesel engine at low temperatures. (1st September 2021) - Shi, Zhicheng; Wu, Han; Li, Haiying; Zhang, Lu; Li, Xiangrong; Lee, Chia-fon
Highlights: Impinging ignition and combustion characteristic in heavy-duty diesel engines. Increased injection pressure helps optimize combustion at high temperatures. Fuel mass required for critical ignition increases linearly with injection pressure. Low injection pressure and large fuel mass helps stable ignition at low temperatures. Abstract: Wall-impinging ignition has been widely studied, but it is still poorly understood at low temperatures. Thus, visualization experiments are performed in a constant volume combustion chamber using direct photography methods. The results show that the injection pressure effect is highly sensitive to temperature, and increased injection pressure helps optimize combustion at high temperatures but causes ignition instability at low temperatures. With an increase in the injection pressure from 40 MPa to 100 MPa, the ignition delay at 840 K is shortened and then extended, and combustion is optimized at 80 MPa. When the temperature is reduced to 790 K, the ignition is stable after a long time of preparation under 40 MPa injection pressure, but the misfire rate increases sharply with injection pressure. The decreased injection mass is not conducive to low-temperature ignition, as indicated by the significantly increased ignition delay. As the injected mass decreases from 35 to 50 mg to 20–30 mg and then to 15 mg, the ignition changes from stable to unstable and then to misfire. Under the co-effect of injection pressure and fuel mass, the misfires are mainly concentrated in areas of high injection pressure at low fuel mass. The minimum fuel mass required for the critical ignition increases approximately linearly with injection pressure. Therefore, for a heavy-duty diesel engine operating in an extremely cold environment, low injection pressure and large fuel mass contribute to the optimization of combustion and improvement of environmental adaptability.